(untitled) (Orthodontic Journal of Nepal, 2013)
Introduction: It requires great skill and material selection to achieve proper solder joint. It is more difficult to perform when one is working with the base alloy. Similar joint can be achieved by cast joining. But no clinical evaluation has been described in the literature about this technique. Objective: To evaluate the clinical success of cast joining in porcelain fused to base alloy fixed partial denture. Materials & Method: The metal frameworks of long span fixed partial denture that did not fit satisfactorily during metal try-in were sectioned through pontics. The pontics were grossly reduced and designed to achieve mechanical interlocking. Then they were connected by self-cure acrylic resin in the patients’ mouth after achieving proper fit. They were reinvested in casting rings and recasting was done. After further try-in, ceramic application were completed and cemented in patients’ mouth. Marginal fit, cervical caries, mechanical strength and metal ceramic bond in joined areas were clinically assessed using Ryge Clinical Criteria. Result: 15 patients were available for follow up. Each patient had worn the fixed partial denture for more than a year. When clinically assessed the marginal fits were acceptable. None of the patients had any cervical caries. None of the fixed partial denture had failed mechanically. There were no cases of ceramic fracture in the pontics areas. Conclusion: Cast joining could be one of the alternative techniques of soldering and welding in fixed partial denture provided that the split is done through the pontic area and well designed to achieve maximum mechanical interlocking. DOI: http://dx.doi.org/10.3126/ojn.v3i1.9284 Orthodontic Journal of Nepal, Vol.3, No.1, 2013: 58-62